Being young female Muslims in Islamic fictions: Moral anxiety, faith primacy and ideal image discourse - Rani Dwi Putri (Universitas Trunojoyo Madura, 2021)
This article examines the representation of Indonesian young female Muslims in Asma Nadia’s works. While previous studies have drawn dynamic transition in real life, this study provides an alternative narrative of being a young female Muslim in Islamic fiction in the context of simultaneous contemporary development in Indonesia with the raising of public piety. This study employed textual analysis method by making categories based on specific themes and understanding each conversation, storyline, and setting of Nadia’s three works, namely “Assalamualaikum Beijing” (“May Peace Be With You, Beijing”), “Jilbab Traveller: Love Sparks in Korea,” and “OTW Nikah” (“On The Way to Marriage”). The author concludes that Asma Nadia places moral anxiety and faith primacy as a frame young female Muslims experience. Moral anxiety reflects a dilemma of the proper way and advantageous outcome to achieve a successful transition. Faith primacy describes a set of spirits for connecting Islamic values and virtuous roles in each life stage. Furthermore, like many popular cultures containing the ideology of contestation, Asma Nadia’s works also provide a discourse about an ideal image that potentially influences and forms the imagination of readers.